2002
DOI: 10.1542/peds.109.3.457
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Gastric Residuals in the Early Enteral Feeding Advancement of Extremely Low Birth Weight Infants

Abstract: 1) Early enteral feeding could be established in ELBW infants. The critical GRV seems to be above 2 mL/3 mL because there was no significant negative correlation between the mean GRV and V14. 2) Green GR were not negatively correlated with V14 and should not slow down the advancement of feeding volumes in absence of other clinical signs and symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
141
0
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(151 citation statements)
references
References 15 publications
6
141
0
4
Order By: Relevance
“…Establishment of enteral nutrition is a significant challenge for premature infants in the neonatal intensive care unit (NICU) [1,2,3]. Spontaneous meconium evacuation is prolonged in premature infants and meconium retention seems to be associated with a delay in establishing enteral feeds [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Establishment of enteral nutrition is a significant challenge for premature infants in the neonatal intensive care unit (NICU) [1,2,3]. Spontaneous meconium evacuation is prolonged in premature infants and meconium retention seems to be associated with a delay in establishing enteral feeds [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the color of the GRV (green, milky, clear) did not predict feeding intolerance. 28 Nonetheless, the volume of feeding on day 14 did correlate with a higher proportion of episodes of zero GRVs and with predominantly milky gastric residuals. Thus, isolated findings related to gastric emptying alone should not be the sole criteria in initiating, advancing, or withholding feeds.…”
Section: Initiation and Advancement Of Enteral Feedingsmentioning
confidence: 78%
“…According to Ziegler, gastric residuals are very frequent in the early neonatal period and are virtually always benign, that is, not associated with NEC. 27 A 2002 study 28 demonstrated that in ELBW infants, excessive gastric residual volume (GRV) either determined by percent of the previous feed or an absolute volume (>2 or >3 mL) did not necessarily affect feeding success as determined by the volume of total feeding on day 14. Similarly, the color of the GRV (green, milky, clear) did not predict feeding intolerance.…”
Section: Initiation and Advancement Of Enteral Feedingsmentioning
confidence: 99%
“…There is no literature consensus about the amount of residue that is clinically relevant. [32][33][34] Hence, the importance of gastric residuals as a diagnostic sign is declining, since it can be considered more a sign of GI maladaptation than of insurgence of NEC and therefore it is not possible to conclude that bolus feeding exerts a better impact on feeding tolerance than continuous feeding.…”
Section: Resultsmentioning
confidence: 99%